Last rights - Nadel, Barbara (London : Headline, 2005)
Undertaker Francis Hancock, in the London borough of West Ham during a bombing raid on the city in 1940, is accosted by a man who claims to have been stabbed but has no visible wounds, and he feels compelled to investigate when the same man's body turns up in his funeral parlor two days later.
Adult
Keywords: Undertakers and undertaking -- England -- London -- Fiction; Veterans -- England -- London -- Fiction; World War, 1939-1945 -- England -- London -- Fiction; Historical fiction; Mystery fiction; Undertakers and undertaking -- London (England) -- Fiction; Veterans -- London (England) -- Fiction; World War, 1939-1945 -- London (England) -- Fiction; Historical fiction; Mystery fiction